Islam Sebagai Rahmatan Lil Alamin - Ardelia April Soneli; Nadiratul Salsabila; Tiara Amarsa; Olivia Dea Angraini; Wismanto Wismanto; Fitria Mayasari (Pusat Riset dan Inovasi Nasional, 2025)
The background to the Islamic concept as rahmatan lil alamin or mercy for all of nature has a broad and deep meaning. Islam is expected to make a positive contribution to all living creatures and ecosystems on earth, not just limited to Muslims. The challenges faced today, such as the social, economic and environmental crises, demand a deeper understanding and real application of this principle. However, in reality, the understanding and application of this concept is often limited or distorted, thus hampering Islam's role in creating a peaceful, just and prosperous life. The research aims to clarify and expand understanding of the concept of Islam as rahmatan lil alamin and to explore its application in the modern era. This research aims to explore the core values ​​of Islamic teachings that support this concept, including the principles of humanity, tolerance and solidarity. The methods used include literature studies, in-depth interviews with religious and community leaders, as well as case study analysis from various Islamic communities. The research results show that the application of Rahmatan Lil Alamin's values ​​can overcome various social challenges, such as intolerance and discrimination, as well as encourage interfaith dialogue. It is hoped that this research can provide insight and practical recommendations to strengthen the role of Islam in creating a more peaceful and just world